A call for innovation in fetal monitoring during fetal surgery. (3rd May 2022) - Warner, Lindsay L.; Arendt, Katherine W.; Ruano, Rodrigo; Qureshi, M. Yasir; Segura, Leal G.
Abstract: Purpose: A growing number of fetal procedures are performed at specialized fetal care centers for congenital problems that classically would have poor outcomes despite advanced postnatal management. Consistent fetal monitoring is integral to the safety of these challenging and innovative surgeries. However, standardization of fetal monitoring during various forms of fetal surgery has yet to be established. Materials and methods: We searched all articles on literature platforms until August 2019 using the terms "fetal surgery, " "fetal monitoring, " and "fetal interventions." Titles and abstracts were screened by our coauthors to determine the type of fetal monitoring used in these cases. Results: The search identified 1, 625 citations, of which the 50 citations considered most pertinent were included in this review. Conclusions: Fetal monitoring during in utero fetal surgeries continues to be challenging because of limited physical fetal access and technological aspects. Innovations in fetal cardiac monitoring during fetal surgeries have the potential for continuous and high-fidelity hemodynamic and physiologic monitoring, with the goal of early detection and treatment of fetal compromise.